Sistem Penilaian Kinerja Karyawan pada PT. Balam Berlian Sawit, Kecamatan Bangko Pusako, Kabupaten Rokan Hilir-Riau - Dona Alfania; Sehani Sehani (Al-Manar Journal of Economic and Social Studies, 2026)
This paper aims to determine the employee performance appraisal system at PT. Balam Berlian Sawit, Bangko Pusako District, Rokan Hilir Regency, Riau. To increase company productivity, qualified and competent human resources are needed, therefore an effective and efficient performance appraisal system is needed for all employees. The writing method used is descriptive qualitative, data collection through interviews and documentation. Based on observations made, it can be concluded that the employee performance appraisal technique at PT. Balam Berlian Sawit, Bangko Pusako District, Rokan Hilir Regency, Riau, is using the Rating Scales method, this method is known that each aspect of the assessment is given a scale starting from 41-100.